Hypothetical, real, and predicted real willingness to pay in open-ended surveys : experimental results - Botelho, Anabela (2001)
This study reports the results of experiments designed to elicit, within a controlled laboratory environment, hypothetical and real willingness to pay for an environmental educational program using the open-ended question format. By maintaining both the good and the question format constant across the treatments, our experiments overcome the shortcomings of recently reported experimental results, providing a clean test for hypothetical bias in open-ended valuations. Having found a statistically significant difference between the hypothetical and real values, we turn into the question of whether hypothetical valuations may nonetheless provide useful statistical information concerning individuals’ real valuations. This question, which is perhaps the key question in the current state of the debate surrounding the contingent valuation method, is answered affirmatively in this study.